Otitis externa in eight horses – clinical signs, treatment and prognosis. Issue 5 (20th June 2019) - Odelros, Emma; Kendall, Anna; Wulcan, Sofia; Bergvall, Kerstin
Abstract : Background: Otitis externa is rare in horses and the condition is poorly described in the literature. Objective: To describe clinical signs, treatment regimens and prognosis of otitis externa in horses. Animals: Eight horses diagnosed with otitis externa during 2011–2018. Methods: Retrospective review of medical records and follow‐up contact with owners. Results: Common clinical signs seen in affected horses were pruritus, ear discharge and ear droop of affected ears. The most common cytological findings were neutrophils, bacteria and yeast. All horses responded well to treatment; two horses were reported to have recurrent problems. Conclusion and clinical importance: Otitis externa in horses is a rare and treatable condition. The condition may be present for prolonged periods before owners become aware, compromising the welfare of affected horses. Untreated otitis externa is a suggested cause of otitis media and temporohyoid osteoarthropathy, emphasizing the importance of identifying and treating this condition at an early stage. For this reason, clinicians should include a brief inspection of the pinnae and external ear canal in the clinical examination of horses. Abstract : Background – Otitis externa is rare in horses and the condition is poorly described in the literature.Objective – To describe clinical signs, treatment regimens and prognosis of otitis externa in horses.Conclusion and clinical importance – Otitis externa in horses is a rare and treatable condition. The condition may be present for prolonged periods before owners become aware, compromising the welfare of affected horses. Untreated otitis externa is a suggested cause of otitis media and temporohyoid osteoarthropathy, emphasizing the importance of identifying and treating this condition at an early stage. For this reason, clinicians should include a brief inspection of the pinnae and external ear canal in the clinical examination of horses. Résumé: Contexte: L'otite externe est rare chez le cheval et peu décrite dans la littérature. Objectifs: Décrire les signes cliniques, les traitements et le pronostic de l'otite externe chez le cheval. Sujets: Huit chevaux diagnostiqués avec otite externe de 2011 à 2018. Matériel et méthode: Revue rétrospective des données médicales et du suivi avec les propriétaires. Résultats: Les signes cliniques communs des chevaux atteints étaient le prurit, un écoulement auriculaire et abaissement des oreilles touchées. Les données cytologiques les plus fréquentes étaient des neutrophiles, bactéries et levures. Tous les chevaux ont bien répondu au traitement, deux chevaux ont été signalés comme ayant des problèmes récurrents. Conclusion et importance clinique: L'otite externe du cheval est rare et traitable. L'atteinte peut être présente pour des périodes prolongées avant que les propriétaires ne s'en aperçoivent, compromettant le bien être des chevaux touchés. L'absence de traitement d'une otite externe est une cause d'otite moyenne et d'ostéo‐arthropathie temporo‐hyoïde, mettant l'accent sur l'importance d'identifier et de traiter cette atteinte à un stade précoce. Pour cette raison, les cliniciens doivent inclure une inspection rapide des pavillons et des conduits auriculaires externes dans leur examen clinique des chevaux. Resumen: Introducción: la otitis externa es rara en caballos y la enfermedad se describe de manera deficiente en la literatura. Objetivo: describir los signos clínicos, los regímenes de tratamiento y el pronóstico de la otitis externa en caballos. Animales: ocho caballos diagnosticados con otitis externa durante 2011–2018. Métodos y materiales: revisión retrospectiva de historiales médicos y seguimiento tras contacto con los propietarios. Resultados: los signos clínicos comunes que se observaron en los caballos afectados fueron prurito, secreción del oído y orejas afectadas caídas. Los hallazgos citológicos más comunes fueron neutrófilos, bacterias y levaduras. Todos los caballos respondieron bien al tratamiento; dos caballos tuvieron problemas recurrentes. Conclusión e importancia clínica: la otitis externa en caballos es una condición rara y tratable. La condición puede estar presente por períodos prolongados antes de que el dueño sea consciente de la enfermedad, comprometiendo el bienestar de los caballos afectados. La otitis externa no tratada es una causa posible de otitis media y osteoartropatía temporohioidea, por lo que es importante identificar y tratar esta condición en una fase temprana. Por esta razón, los veterinarios deben incluir una breve inspección de las orejas y el canal auditivo externo en el examen clínico de los caballos. Zusammenfassung: Hintergrund: Eine Otitis externa kommt bei Pferden selten vor und dieser Zustand ist in der Literatur nur wenig beschrieben. Ziele: Die Beschreibung der klinischen Zeichen, des Behandungsregimes und der Prognose von Otitis externa bei Pferden. Tiere: Acht Pferde, die zwischen 2011‐2018 mit einer Otitis externa diagnostiziert worden waren. Methoden und Materialien: Eine retrospektive Review der medizinischen Aufzeichnungen und ein Follow‐Up Kontakt mit den BesitzerInnen. Ergebnisse: Häufige klinische Anzeichen, die bei betroffenen Pferden gesehen werden, waren Juckreiz, Ausfluss aus dem Ohr und ein Herunterhängen der betroffenen Ohren. Die häufigsten zytologischen Befunde waren Neutrophile, Bakterien und Hefen. Alle Pferde reagierten gut auf eine Behandung; von zwei Pferden wurde von wiederkehrenden Problemen berichtet. Schlussfolgerung und klinische Bedeutung: Die Otitis externa bei Pferden kommt selten vor und ist eine behandelbare Erkrankung. Die Erkrankung könnte schon einige Zeit bestehen, bevor es den BesitzerInnen bewußt wird, was das Wohlergehen des Pferdes beeinträchtigen kann. Eine unbehandelte Otitis externa könnte die Ursache für eine Otitis media und einer temporohyoiden Osteoarthropathie sein, was die Wichtigkeit einer Diagnose und einer Behandlung dieser Erkrankung in einer frühen Phase verdeutlicht. Aus diesem Grund sollten KlinikerInnen eine kurze Untersuchung der Pinnae und des externen Ohrkanals bei einer klinischen Untersuchung des Pferdes inkludieren. 要約: 背景: 外耳炎は馬にはまれであり、その疾患に対する文献の記述は乏しい。 目的: 本研究の目的は、馬の臨床的徴候、治療計画および外耳炎の予後について記述することである。 被験動物: 2011年 ‐ 2018年に外耳炎と診断された馬8頭。 材料と方法: 医療記録の回顧的レビューと所有者に対するフォローアップの連絡。 結果: 罹患馬に見られる共通の臨床徴候は、罹患耳の掻痒、耳の排膿および耳の垂れ下がりであった。最も一般的な細胞学的所見は、好中球、細菌、酵母であった。すべての馬が治療によく反応した。 しかし、2頭の馬において再発に対する問題があると報告があった。 結論と臨床的重要性: 馬の外耳炎はまれで治療可能な疾患である。この疾患は、飼い主が気付く前に長期間にわたって存在し、罹患馬の幸福を危険にさらす可能性がある。未治療の外耳炎は、中耳炎および側頭舌骨変形性関節症の原因として示唆されており、早期にこの疾患を特定し治療することの重要性を強調している。このため、臨床医は馬の臨床検査に耳介と外耳道の簡単な検査を含めるべきである。 摘要: 背景: 马的外耳炎很罕见, 并且很少有文献报道。 目的: 描述马外耳炎的临床症状、治疗方案和预后。 动物: 2011年至2018年间, 被确诊患有外耳炎的八匹马。 方法和材料: 回顾性审查病例, 并向主人进行随访。 结果: 观察到患马常见临床症状是耳朵瘙痒、有分泌物和患耳下垂。细胞学最常见的结果是中性粒细胞、细菌和酵母菌。据报道, 除了两匹马反复出现问题, 其它马匹对治疗均反应良好。 结论和临床价值: 马外耳炎是一种罕见且可治疗的症状, 这种情况可能会在主人发现前很长时间就存在, 从而损害患病马匹的福利。未经治疗的外耳炎可能会导致中耳炎和颞叶骨关节病, 这也强调了在早期识别和治疗这种症状的重要性。因此, 临床医生在马的检查中, 应该包括对耳廓和外耳道的快速检查。 Resumo: Contexto: A otite externa em equinos é rara e pouco descrita na literatura. Objetivo: Descrever os sinais clínicos, protocolos de tratamento e prognóstico da otite externa em cavalos. Animais: Oito cavalos diagnosticados com otite externa entre 2011‐2018. Métodos e materiais: Revisão retrospectiva dos prontuários e contato com os proprietários. Resultados: Os sinais clínicos comumente observados nos cavalos afetados foram prurido, secreção auricular e queda das orelhas afetadas. Os achados citológicos mais comuns foram neutrófilos, bactérias e leveduras. Todos os cavalos responderam bem ao tratamento; relatou‐se problemas recorrentes em dois equinos. Conclusões e importância clínica: A otite externa em cavalos é uma condição rara e tratável. A doença pode estar presente por longos períodos sem que o proprietário perceba, afetando o bem‐estar dos equinos acometidos. Sugere‐se que a otite externa não tratada seja uma causa de otite média e osteoartropatia temporo‐hióide, enfatizando a importância da identificação e do tratamento da doença em estágios iniciais. Por esta razão, os clínicos devem incluir uma breve inspeção dos pavilhões auriculares e do conduto auditivo externo no exame clínico de cavalos.